2008
DOI: 10.1016/j.toxlet.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Further insight into the impact of sodium selenite on selenoenzymes: High-dose selenite enhances hepatic thioredoxin reductase 1 activity as a consequence of liver injury

Abstract: Selenium (Se) at supranutritional levels can enhance the activity of glutathione S-transferase (GST), whose gene is a target of nuclear factor erythroid-2 related factor 2 (Nrf2). Recent studies indicated that the thioredoxin reductase 1 (TrxR1) gene could also be targeted by Nrf2. Thus, high-dose Se may stimulate TrxR1 provided it enhances GST activity. Indeed, one study found that Se at supranutritional levels transiently increased hepatic TrxR1 activity. However, another study reported that supranutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 36 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…The role of GST is reflected in detoxification, transport, and synthesis, and this is one of the oxidative stress inducible enzymes. Zhang and associates [47] showed that at supranutritional levels, Se could enhance hepatic GST activity. Opposite to these data, our results indicate synergistic inhibitory effects of Se and cisPt on GST activity in RBC.…”
Section: Discussionmentioning
confidence: 99%
“…The role of GST is reflected in detoxification, transport, and synthesis, and this is one of the oxidative stress inducible enzymes. Zhang and associates [47] showed that at supranutritional levels, Se could enhance hepatic GST activity. Opposite to these data, our results indicate synergistic inhibitory effects of Se and cisPt on GST activity in RBC.…”
Section: Discussionmentioning
confidence: 99%
“…20 Compared with several extensively studied selenium compounds, ie, sodium selenite, selenomethionine, and methylselenocysteine, selenium nanoparticles show markedly lower acute toxicity and significantly lower short-term and subchronic toxicities, but all these selenium compounds have equivalent efficacy in their ability to increase selenoenzymes. [20][21][22][23][24][25] Furthermore, selenium nanoparticles appear to be more efficient than sodium selenite and selenomethionine in increasing glutathione S-transferase activity, 21,25 and seem to be equally efficient in inducing apoptosis of certain types of cancer cells as methylseleninic acid, a metabolite of methylselenocysteine that is considered to be the most promising selenium compound in cancer prevention. 26 Selenium nanoparticles may enhance selenium permeation and retention in tumor tissues because their blood vessels contain enlarged pore sizes ranging from 100 nm to 800 nm, in stark contrast with the pore sizes of 2 nm to 6 nm in the vessels of healthy tissues.…”
Section: Introductionmentioning
confidence: 99%
“…28 Selenium nanoparticles have emerged as a novel selenium source with the obvious advantage of reduced risk of selenium toxicity. [20][21][22][23][24][25]29,30 Accordingly, a selenium nanoparticle solution may be added to functional foods, the final products of which may be subjected to heat during processing. An important feature of nanoparticles is their high surface to volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…After 2-10 days their levels returned to normal values. Zhang et al [27] exposed mice to Se for 14 days with an i.p. injection of 2 mg selenite/kg bw and found a significant increase in the activities of ALT and AST, a decrease in the liver glutathione peroxidase and SOD, and an increase in GST and Thioredoxin Reductase.…”
Section: Discussionmentioning
confidence: 99%